A SPATIAL ANALYSIS OF CRIMES AGAINST THE PERSON IN THE CITY ERZINCAN (2017) - Vedat KARADENİZ (Fırat University, 2020)
Crime, which is as old as the history of humanity, is a phenomenon affecting societies with its causes and consequences. There are many factors that cause crime and interact with each other. These factors are handled by various disciplines and studies are being conducted to prevent crime. One of these disciplines is geography and tries to explain the role of space in crime formation. There is no doubt that crime takes place on a piece of space. The distribution of crime in space, its connections with other events and the cause-effect relationship and distribution are within the scope of geography. The number of crimes committed in the settlement centers is directly related to the population. The greater the population in a settlement, the higher the likelihood of committing a crime. In this respect, with the cosmopolitan structure and population, the cities have higher capacities to produce crime than rural settlements. Its wealth, alienation and weakening social control mechanisms provide an ideal environment for committing crime in cities. One of these settlements is the city of Erzincan. In this study, the types of crimes that occurred in the city of Erzincan and the crimes committed against the most common ones were examined. The distribution of crimes against the person and the socio-spatial differences affecting this distribution are examined. For this purpose, the crime statistics of 2017 were used. In the light of the data obtained, the relationship between the types of crimes committed against the person and urban land use and socioeconomic characteristics were discussed. Crime events were examined in terms of time and space and interpreted from a geographical point of view.